Evidence of linkage to chromosome 5p13.2‐q11.1 in a large inbred family with genetic generalized epilepsy - Kinay, Demet; Oliver, Karen L.; Tüzün, Erdem; Damiano, John A.; Ulusoy, Canan; Andermann, Eva; Hildebrand, Michael S.; Bahlo, Melanie; Berkovic, Samuel F. (Epilepsia (Copenhagen), 2018)
Summary The clinical genetics of genetic generalized epilepsy suggests complex inheritance; large pedigrees, with multiple affected individuals, are rare exceptions. We studied a large consanguineous family from Turkey where extensive electroclinical phenotyping revealed a familial phenotype most closely resembling juvenile myoclonic epilepsy. For a subject to be considered affected (n = 14), a diagnostic electroencephalogram was required. Seizure onset ranged between 6 and 19 years (mean = 12 years). Thirteen of 14 experienced myoclonic jerks; in 11, this was associated with eyelid blinking, and in 10 it was interspersed with absences. Generalized tonic–clonic seizures were seen in 11. One individual had generalized tonic–clonic seizures alone. Electroencephalograms demonstrated generalized polyspike and wave discharges that were not associated with photoparoxysmal response. Intellect was normal. Nineteen family members were subsequently chosen for nonparametric multipoint linkage analyses, which identified a 39.5 Mb region on chromosome 5 (P < 0.0001). Iterative analysis, including discovery of a subtly affected individual, narrowed the critical region to 15.4 Mb and possibly to 5.5 Mb. Homozygous versus heterozygous state of the refined 5p13.2‐q11.1 haplotype was not associated with phenotypic severity or onset age, suggesting that one versus two pathogenic variants may result in similar phenotypes. Whole exome sequencing (n = 3) failed to detect any rare, protein‐coding variants within the highly significant linkage region that includes HCN1 as a promising candidate.